To Explore the Relationship Between Internalized Misogyny and Career Choices among Indian Women - Ishaani Jha; Dr. Anjali Sahai Srivastava (International Journal of Indian Psychȯlogy, 2022)
The quantitative research paper delves into the relationship between internalized misogyny and career choices among Indian women. The study aims to investigate how internalized misogyny influences the career decisions of Indian women, focusing on a sample of 47 working women in an urban metropolitan city. The research utilizes the Internalized Misogyny Scale (IMS) and the Career Aspiration Scale-Revised (CAS-R) to assess internalized devaluation of women and career aspirations, respectively. Results from the study reveal insights into the impact of internalized misogyny on women’s career choices. The paper emphasizes the importance of recognizing and addressing internalized misogyny to empower women and promote gender equality in professional settings.